Hybrid coding for image compression - Praba, V. Lakshmi; Rajesh, RS; Anitha, S (International Journal of Computer Sciences and Engineering, 2025)
Image compression take a important part in digital world. Storing and transmitting digital image with high quality is a complex task. There are many methods for compressing digital images. In this paper, the following method is adapted. The digital image is divided into low and high intensity images. Discrete Cosine Transform (DCT) technique is applied to high intensity part of the image and fast Fourier transform (FFT) method is applied for low intensity pixels. The proposed method is tested with benchmark images and the results are compared with JPEG 2000 (Joint Photographic Experts Group 2000). It provides better results than JPEG 2000.